PENGEMBANGAN SANTRIPRENEURSHIP BERBASIS BUDIDAYA JAMUR TIRAM DAN PENGOLAHAN PASCA PANEN - Yusril - Maulana; Putri - Sekarudya; Saiful - Fakrur; Muhammad - Adil (Admisi dan Bisnis, 2019)
Islamic boarding schools basically have the task of guiding and being responsible for the survival of their students. However, the existence of Islamic boarding schools is often hit by various issues related to service limitations such as the absence of a fixed source of funds, limited facilities, and lack of professional staff. Therefore, entrepreneurship skills training is needed so that the santri can become independent, productive, and Islamic boarding schools will have a new source of income to help with operational costs every month. Oyster Mushroom Cultivation is here to answer the above problems because the prospect of Oyster Mushroom is quite good, maintenance is easy, does not require extensive land, and is much in demand by the community. The target of this service program is the santriawan and santri students of the Nurul Hikmah Islamic Boarding School and boarding school officials because they are ready to receive training in outline mushroom cultivation, the program to be implemented is gradual and continuous training and mentoring starting from planting, care, harvest to marketing. The marketing method used is conventional marketing and online marketing through the website and various social networks, because besides being able to save costs, energy, and of course online marketing can also increase the reach or marketing area